The Effectiveness of Pomodoro Technique on Students' Descriptive Text Writing Quality - Widya Eka Septiani; Sulistyaningsih Sulistyaningsih; Abd. Syakur (Jurnal Basicedu, 2022)
This research was conducted by the aim to investigate the effectiveness of Podomoro technique in teaching descriptive text at junior high school at Sidoarjo. The design of this quasi-experimental type was pre-test and post-test non-equivalent control group design. The results of the data reliability test showed that the research instrument was reliable because the Cronbach's alpha value was 0.653 and more than 0.6. Furthermore, it showed the experiment group pretest score was 77.20, control group was 79.00. The experimental group's mean was frequently lower than the control group. The experimental group’s mean post-test score was 87.40, whereas the control group was 79.20. The experimental group’s post-test mean was higher than the control group. The researcher next calculated the mean of the experimental and control groups by t-test (paired sample test) to see if the scores before and after the treatment were significant. It indicated that the pomodoro technique was beneficial in assisting the students in improving their writing skills.